STEPAN BANDERA IN THE SOVIET VERSION OF HISTORY (Південний архів (історичні науки), 2022)
The research aims at exploring Stepan Bandera’s charachter through the lens of the Soviet reading of history. After all, interest towards Bandera has not been fading for half a century and as an outcome a significant amount of scholarly studies of OUN-B’s leader has accumulated. Myth-making about Bandera has been particularly in focus of the Soviet propaganda with the historians’ contribution. Hence, grasping the roots of the myths would enhance tolerant treatment of the past by contemporary Ukrainian society as well as strengthen the unique Ukrainian identity. The research is undertaken through application of general (analytical-synthetic, chronological and generalisation methods) and specialised historical methods such as historicaltypological, historical-biographic methods that constitute the foundation of the research and contribute to rigorous assessment of the Soviet interpretation of Stepan Bandera's figure. Findings. The scholarly literature review has demonstrated depiction of OUN-B’s leader either in emotional lens or his complete disregard. Most significant scholarly research does not contain a single mentioning of Stepan Bandera’s name, however their pages are full of brutal “Banderovits” and Ukrainian bourgeois nationalists’ depiction. The key explanation for demonizing the leader was his principled struggle against the Stalinist regime. Conclusions. In the postwar decade, Stepan Bandera’s negative image was enhanced by the propaganda literature published with the goal of satisfying the requirements of the state security apparatus. Bandera’s figure was tied to a set of entrenched labels as cooperation with Nazis. In the second half of the XX century a Soviet interpretation of Ukrainian nationalism as «the greatest enemy of the Ukrainian people» took its final shape. Its features are ideological obscurantism, distortion and concealment of facts and hatred towards OUN-B’s leading personalities. As for Stepan Bandera, the genralised notion of Bandera and “banderovits” was in common use in scholarly works which led to his ignorance by historians.
Keywords: OUN(b) leader, historical figure, Soviet concept, scientific dimension, propaganda.